Practical Electricity - Croft, Terrell (McGraw-Hill Book Company, 1917)
First edition volume written by Terrell Croft (1880-1967), an American engineer and author of many technical books on electrical and mechanical subjects. The fully illustrated publication was written "to present the fundamental facts and theories relating to electricity and its present-day applications" for any curious reader with little technical knowledge. The text is focused on the theory and principles of electricity and magnetism. The digitized content of the work includes the covers, front matter, preface, table of contents, and two figures depicting telegraphic systems.
Keywords: Communication; Communication and technology; Electrical engineering; Electricity; Telecommunication; Electromagnetism; Electromagnetism--Study and teaching